KETERHUBUNGAN ANTARA FAKTOR GANGGUAN MENSTRUASI MAHASISWI STKIP PASUNDAN CIMAHI - Faradis, Mega (Jurnal Olahraga, 2015)
Menstrual disorders are a problem that is often found with the highest prevalence in late teens. If not treated, menstrual disorders can affect the quality of life and daily activities. Research on menstrual disorders in adolescents has not been done much in Indonesia. The purpose of this study was to determine how much the relationship between menstrual disorders in the Department of Sport and related factors. A cross sectional study was conducted on 57 STKIP Pasundan female students from the PJKR Department, using a questionnaire filled with guidance from researchers. Obtained respondents aged 18-22 years who are mostly Level I students (43.9%). Almost all (98.2%) of respondents experienced their first menstruation in the age range of 11-14 years. Most (66.7%) respondents have normal nutritional status. More than half (54.4%) of respondents were physically active. There were 63.2% of respondents who experienced menstrual disorders with the most types of disorders (91.7%) were other disorders related to menstruation, followed by menstrual disorders (25.0%), and menstrual cycle disorders (5.0%). There were no respondents who experienced menstrual volume disorders. Among respondents with other disorders related to menstruation, premenstrual syndrome was the most experienced (75.8%). There is a significant relationship between age, class, and physical activity with menstrual disorders. There is no significant relationship between the age of first menstruation and nutritional status with menstrual disorders